2015
DOI: 10.1208/s12248-015-9797-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of In Vivo Clinical Product Performance of a Weak Basic Drug by Integration of In Vitro Dissolution Tests and Physiologically Based Absorption Modeling

Abstract: Abstract. Effective integration of in vitro tests and absorption modeling can greatly improve our capability in understanding, comparing, and predicting in vivo performances of clinical drug products. In this case, we used a proprietary drug candidate galunisertib to describe the procedures of designing key in vitro tests, analyzing relevant experimental and trial data, and integrating them into physiologically based absorption models to evaluate the performances of its clinical products. By simulating the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The compound demonstrated the highest solubility near pH 2, which corresponds to the fasted stomach pH, and maintained favorable solubility and dissolution properties for absorption at pH 4.5 and pH 7.5, as observed in duodenal and intestinal fluids. When these solubility data were applied to a gastroduodenal passage model (39), the simulation predicted that LY3023414 would closely approach the theoretical maximum absorption in contrast to other PI3K/mTOR dual inhibitors (i.e., NVP-BEZ-235 and PF04691502; see Supplementary Fig. S1), whereas absorption would be only slightly reduced by coadministration of gastric pH-altering proton-pump inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…The compound demonstrated the highest solubility near pH 2, which corresponds to the fasted stomach pH, and maintained favorable solubility and dissolution properties for absorption at pH 4.5 and pH 7.5, as observed in duodenal and intestinal fluids. When these solubility data were applied to a gastroduodenal passage model (39), the simulation predicted that LY3023414 would closely approach the theoretical maximum absorption in contrast to other PI3K/mTOR dual inhibitors (i.e., NVP-BEZ-235 and PF04691502; see Supplementary Fig. S1), whereas absorption would be only slightly reduced by coadministration of gastric pH-altering proton-pump inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…In these in vitro experiments, the PK profiles of the RC formulations were similar to that of the HSWG formulation [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Galunisertib is well absorbed with peak plasma concentrations attaining around 0.5–2 hours following administration and with mean terminal half-life of 8 hours [8]. The effect of gut pH on galunisertib absorption has been studied previously, where we reported that galunisertib in solution or tablet products maintained supersaturation during transit in the gastrointestinal tract [9]. To reduce the impact of change in pH after a meal, galunisertib has thus far been administered to patients only in fasted state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial starting volumes in the chambers, the flow rate of fresh media into the chambers and the emptying rate from the chambers can all be adjusted to fit the experimental requirements (e.g. in vitro modelling of fasted/fed state, human or dog model) . Dilute HCl and Level II FaSSIF are typically used as gastric and duodenal fluid, respectively.…”
Section: Compartmental Methods Using Cellular Membranesmentioning
confidence: 99%